Micro-fluidic crack chip based on transparent calcite and preparation method of micro-fluidic crack chip
By using transparent calcite materials to prepare microfluidic crack chips, etching the crack channels and connecting the substrate, the problems of inconsistency in existing chip materials and complex production are solved, and efficient microfluidic experimental simulation and real rock characteristics are achieved.
Patent Information
- Application Number
- CN202411771293.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-04-18
AI Technical Summary
The upper and lower base layers of existing microfluidic chips are inconsistent with the main material of the chip, which cannot reflect the real rock characteristics, and the production process is complicated.
A microfluidic crack chip is prepared using transparent calcite materials. By etching the crack channel on the calcite matrix and connecting the lower substrate and the upper substrate of the chip with an adhesive layer, the simulation of the true rock characteristics is achieved.
It realizes the microfluidic chip's visualization effect, excellent sealing, small dose of test liquid and high accuracy, and can accurately simulate the physical and chemical characteristics of real rocks, simplifying the production process.
Smart Images

Figure CN119838646A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of microfluidic fracture chips, and in particular relates to a microfluidic fracture chip based on transparent calcite and a preparation method thereof. Background Art
[0002] In the field of geology and energy, the deposition and dissolution process in fractures is of great significance for improving oil and gas recovery, geological storage of carbon dioxide, and groundwater pollution control. The migration and deposition of sediments in fractures will significantly affect the connectivity and effective permeability of fluid flow channels, thereby affecting the stability of resource extraction and geological storage.
[0003] Although traditional research methods such as magnetic resonance imaging (MRI) and computed tomography (CT) can provide three-dimensional observation data, they still have limitations in real-time analysis of pore-scale fluid-solid coupling interactions. Microfluidics technology has been widely used in multiphase flow research in recent years because it can accurately manipulate and observe fluid behavior at the microscopic scale. However, most of the existing microfluidic chips use chemically inert materials (such as glass or silicon), which makes it difficult to simulate the physical and chemical properties of real rocks. In the prior art, a microfluidic chip for chemical dissolution research in geological processes is disclosed (patent number ZL201910238487.X). The chip structure mainly includes a microfluidic chip body, upper, middle and lower base channel etching, and bonding and packaging of the upper, middle and lower bases with the microfluidic chip body. The disadvantage is that the upper and lower base materials are inconsistent with the chip body material, cannot reflect the real rock characteristics, and the manufacturing process is more complicated. Therefore, it is of great research significance to develop a microfluidic chip model based on the real rock fracture structure. Summary of the invention
[0004] The purpose of the present invention is to address the above-mentioned deficiencies in the prior art and to provide a microfluidic fracture chip based on transparent calcite and a method for preparing the same, so as to solve the problems that the upper and lower substrates of the existing microfluidic chip are inconsistent with the chip body material, cannot reflect the real rock properties, and have a complicated manufacturing process.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] In a first aspect, a microfluidic fracture chip based on transparent calcite comprises a lower chip substrate and an upper chip substrate; an adhesive layer is provided on the lower chip substrate, and the lower chip substrate is connected to the upper chip substrate through the adhesive layer;
[0007] A crack channel is etched inside the substrate under the chip; a fluid inlet and a fluid outlet that do not pass through the substrate under the chip are respectively opened at both ends of the crack channel; a fluid inlet and a fluid outlet that pass through the substrate on the chip are respectively opened on the substrate on the chip, and two fluid interfaces corresponding to the fluid inlet and fluid outlet are installed on the substrate on the chip.
[0008] Furthermore, the material of the substrate under the chip and the substrate on the chip are both transparent calcite.
[0009] In a second aspect, a method for preparing a microfluidic fracture chip based on transparent calcite comprises the following steps:
[0010] S1, selecting a natural transparent calcite crystal, cutting and polishing the transparent calcite crystal to obtain a chip lower substrate and a chip upper substrate;
[0011] S2, evenly coating the acid-resistant protective wax film on the surface of the substrate under the chip;
[0012] S3, arranging a crack pattern on the surface of the substrate under the chip, using a laser etcher to carve crack channels on the acid-resistant protective wax film, and exposing the etching area where the crack channels are located;
[0013] S4, immersing the substrate under the chip in a hydrochloric acid solution, and controlling the flow of the hydrochloric acid solution by stirring at a low speed until a crack channel is etched;
[0014] S5, taking out the substrate under the chip, cleaning the substrate under the chip with deionized water, and removing the acid-resistant protective wax film;
[0015] S6, drilling a fluid inlet and a fluid outlet at both ends of the crack channel of the substrate under the chip using a precision drilling controller;
[0016] S7, evenly coating marble glue on the non-channel surface area of the substrate under the chip to form an adhesive layer;
[0017] S8, drilling a fluid inlet and a fluid outlet on the substrate on the chip using a precision drilling controller;
[0018] S9, connecting the lower substrate of the chip and the upper substrate of the chip through an adhesive layer, and applying pressure to bond the lower substrate of the chip and the upper substrate of the chip to prepare a crack chip;
[0019] S10, installing fluid interfaces at the fluid inlet and fluid outlet on the surface of the substrate on the chip respectively;
[0020] S11, injecting deionized water into the crack chip through the fluid inlet, and verifying the sealing and fluid flow performance of the channel by low pressure;
[0021] S12. Clean the qualified fracture chip with deionized water and acetone to remove the residual substances in the fracture chip and obtain a real rock fracture microfluidic chip.
[0022] Furthermore, the S1 specifically includes:
[0023] The selected natural transparent calcite crystals were cut into crystal slices with a size of 2 cm×4 cm and a thickness of 3 mm using a slice cutter, and the crystal slices were surface-polished to obtain a chip lower substrate and a chip upper substrate.
[0024] Furthermore, the length of the crack channel in S3 is 3 cm and the depth is 1 mm.
[0025] Furthermore, the S4 specifically includes:
[0026] The substrate under the chip is immersed in the hydrochloric acid solution, and the flow of the acid solution is controlled by stirring at 10 rpm / min. The etching time is controlled to be 10 to 15 minutes until the etching depth and shape reach the expected depth and shape.
[0027] Furthermore, the depth of the fluid inlet and the fluid outlet drilled in S6 is located at the outer wall of the fracture channel and does not penetrate the substrate under the chip.
[0028] Furthermore, the fluid inlet and fluid outlet drilled in S8 pass through the substrate on the chip.
[0029] Furthermore, the S11 specifically includes:
[0030] Deionized water was injected into the fluid inlet of the fracture chip, and an initial pressure of 0.1 MPa was applied;
[0031] Close the fluid outlet, keep the water pressure in the crack chip stable, record the initial pressure, and monitor the pressure decay value in the chip in real time;
[0032] If the pressure decay value is less than 5% within 30 minutes, and the average pressure decay value is within 5% after the sealing test is repeated 3 times, the crack chip has good sealing performance;
[0033] The fluorescence tracer method is used to observe the uniformity and speed of the ionized water flow. Fluorescent dye is added to deionized water and injected into the fracture channel. The flow of the ionized water fluid in the channel is observed under a fluorescence microscope. If the flow trajectory of the fluorescent dye is smooth and uniform, and there is no stagnation or backflow, it is judged that the fluidity in the fracture channel meets the requirements.
[0034] The transparent calcite-based microfluidic crack chip and its preparation method provided by the present invention have the following characteristics:
[0035] Beneficial effects:
[0036] 1. The microfluidic fracture chip of the present invention has the advantages of good visualization effect, excellent sealing, small test liquid dosage, high precision, etc. It uses transparent calcite material, which not only has high light transmittance, but also has excellent visualization effect, and can realize real-time observation and quantitative analysis of the interaction between multiphase fluid and sediment in the fracture.
[0037] 2. The present invention uses calcite material to retain the physical and chemical properties of real rocks, thereby accurately simulating the acid dissolution and sedimentation process.
[0038] 3. The present invention uses high-resolution micro-CT to obtain the characteristics of natural cracks, and uses laser etching technology to accurately control the shape and size of the crack channels, which can accurately describe the natural geometric characteristics and improve the authenticity and applicability of the experiment.
[0039] 4. The crack chip preparation method provided by the present invention has simple manufacturing process, short preparation time, high etching precision, good packaging effect, and is easy to realize mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 It is a schematic diagram of the structure of the microfluidic fracture chip based on transparent calcite of the present invention.
[0041] Figure 2 It is a schematic diagram of the lower substrate of the microfluidic crack chip of the present invention.
[0042] Figure 3 Schematic diagram of the substrate on the microfluidic slit chip of the present invention.
[0043] Among them, 1. substrate under the chip; 2. crack channel; 3. substrate on the chip; 4. adhesive layer; 5. fluid inlet; 6. fluid outlet; 7. fluid interface. DETAILED DESCRIPTION
[0044] The specific implementation modes of the present invention are described below so that those skilled in the art can understand the present invention. However, it should be clear that the present invention is not limited to the scope of the specific implementation modes. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention as defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the concept of the present invention are protected.
[0045] Example 1
[0046] The microfluidic crack chip based on transparent calcite in this embodiment is shown in FIG. Figure 1 and Figure 2 , which includes:
[0047] The lower chip substrate 1 and the upper chip substrate 3 are both made of transparent calcite.
[0048] Wherein, an adhesive layer 4 is provided on the lower chip substrate 1, and the lower chip substrate 1 is connected to the upper chip substrate 3 via the adhesive layer 4, and the material of the adhesive layer 4 is made of marble glue.
[0049] A crack channel 2 is etched inside the chip substrate 1, and the two ends of the crack channel 2 are respectively provided with a fluid inlet 5 and a fluid outlet 6 that do not pass through the chip substrate 1, and the chip substrate 3 is respectively provided with a fluid inlet 5 and a fluid outlet 6 that pass through the chip substrate 3; in this embodiment, the fluid inlet 5 and the fluid outlet 6 of the chip substrate 3 correspond to the fluid inlet 5 and the fluid outlet 6 respectively opened in the chip substrate 1.
[0050] To facilitate the injection and control of the fluid, two fluid interfaces 7 corresponding to the fluid inlet 5 and the fluid outlet 6 are installed on the substrate 3 on the chip in this embodiment.
[0051] As a preferred embodiment of the present invention, the size of the lower chip substrate 1 and the upper chip substrate 3 are both 2 cm×4 cm and 3 mm thick;
[0052] As a preference of this embodiment, the diameters of the fluid inlet 5 and the fluid outlet 6 are designed to be 1 mm.
[0053] Example 2
[0054] This embodiment is based on Embodiment 1 and provides a method for preparing a microfluidic fracture chip based on transparent calcite, which comprises the following steps:
[0055] Step S1, selecting a natural transparent calcite crystal, and using a thin slice cutting machine to cut the transparent calcite crystal into crystal slices with a size of 2 cm×4 cm and a thickness of 3 mm, and performing surface polishing on the crystal slices to obtain a chip lower substrate 1 and a chip upper substrate 3;
[0056] Step S2, uniformly coating an acid-resistant protective wax film on the surface of the obtained chip lower substrate 1;
[0057] Step S3: Reference Figure 2 , a crack pattern is arranged on the surface of the processed chip lower substrate 1, and a crack channel 2 is engraved on the wax film using a laser etcher, the crack channel 2 is 3 cm long and 1 mm deep, ensuring that the etched area exposes the calcite crystals while the unetched area is protected;
[0058] Step S4: Reference Figure 2 , the obtained chip lower substrate 1 is immersed in a hydrochloric acid solution, the acid solution flow is controlled by stirring at 10 rpm / min, the channel formation process is monitored during the etching process, and the etching time is controlled within 10 to 15 minutes to achieve the desired depth and shape;
[0059] Step S5, taking out the processed chip lower substrate 1, washing it with deionized water, and removing the acid-resistant protective wax film;
[0060] Step S6, using a precision drilling controller to drill a fluid inlet 5 and a fluid outlet 6 at both ends of the crack channel 2 of the chip lower substrate 1, to ensure that the hole depth just reaches the outer wall of the crack channel 2 without penetrating through it, so as not to damage the integrity of the channel;
[0061] Step S7, evenly coating the non-channel surface area of the chip lower substrate 1 with marble glue to form an adhesive layer 4, while protecting the interior of the crack channel 2 from being contaminated by the marble glue;
[0062] Step S8: Reference Figure 3 , using a high-precision drilling machine to drill the fluid inlet 5 and the fluid outlet 6 at the same position on the substrate 3 on the chip, and drilling through the substrate 3 on the chip;
[0063] Step S9, pressing and bonding the lower substrate 1 and the upper substrate 3 of the chip in a timely manner to ensure no leakage, thereby obtaining a crack chip;
[0064] Step S10, installing a fluid interface 7 at the fluid inlet 5 and the fluid outlet 6 of the crack chip to facilitate fluid control and injection;
[0065] Step S11, inject deionized water through the fluid inlet 5, apply an initial pressure of 0.1 MPa, close the fluid outlet 6, and keep the water pressure in the chip stable; record the initial pressure, and then monitor the pressure decay in the chip, usually for 30 minutes or 1 hour;
[0066] If the pressure decay value is less than 5% (i.e., reduced from 0.1MPa to within 0.095MPa) within 30 minutes, the sealing test should be repeated 3 times, and the average pressure decay value should be within 5%, then the chip can be considered to have good sealing performance;
[0067] Use the fluorescence tracer method to observe the uniformity and speed of fluid flow. Add an appropriate amount of fluorescent dye to deionized water and inject it into the fracture channel 2. Observe the flow of the fluid in the channel under a fluorescence microscope. If the dye flow track is smooth and uniform, and there is no stagnation or backflow, it indicates that the fluidity in the channel is good.
[0068] Step S12: Clean the qualified fracture chip with deionized water and acetone to ensure that there is no residual material inside the channel, so as to obtain a real rock fracture microfluidic chip.
[0069] Although the specific implementation of the invention is described in detail in conjunction with the drawings, it should not be understood as limiting the scope of protection of this patent. Within the scope described in the claims, various modifications and variations that can be made by those skilled in the art without creative work still fall within the scope of protection of this patent.
Claims
1. A microfluidic fracture chip based on transparent calcite, characterized in that: It comprises a lower chip substrate (1) and an upper chip substrate (3); an adhesive layer (4) is provided on the lower chip substrate (1), and the lower chip substrate (1) is connected to the upper chip substrate (3) via the adhesive layer (4); A crack channel (2) is etched inside the lower chip substrate (1); a fluid inlet (5) and a fluid outlet (6) that do not pass through the lower chip substrate (1) are respectively opened at both ends of the crack channel (2); a fluid inlet (5) and a fluid outlet (6) that pass through the upper chip substrate (3) are respectively opened on the upper chip substrate (3), and two fluid interfaces (7) corresponding to the fluid inlet (5) and the fluid outlet (6) are installed on the upper chip substrate (3).
2. The transparent calcite-based microfluidic fracture chip according to claim 1, characterized in that: The material of the under-chip substrate (1) and the on-chip substrate (3) are both transparent calcite.
3. A method for preparing a transparent calcite-based microfluidic fracture chip according to claim 1 or 2, characterized in that: The following steps are involved: S1, selecting a natural transparent calcite crystal, cutting and polishing the transparent calcite crystal to obtain a lower chip substrate (1) and an upper chip substrate (3); S2, evenly coating the surface of the substrate (1) under the chip with an acid-resistant protective wax film; S3, arranging a crack pattern on the surface of the substrate (1) below the chip, using a laser etcher to carve a crack channel (2) on the acid-resistant protective wax film, and exposing the etching area where the crack channel (2) is located; S4, immersing the substrate (1) below the chip into a hydrochloric acid solution, and controlling the flow of the hydrochloric acid solution by stirring at a low speed until a crack channel (2) is etched; S5, taking out the chip lower substrate (1), washing the chip lower substrate (1) with deionized water, and removing the acid-resistant protective wax film; S6. Using a precision drilling controller, a fluid inlet (5) and a fluid outlet (6) are drilled at both ends of the crack channel (2) of the substrate (1) below the chip; S7, evenly coating marble glue on the non-channel surface area on the substrate (1) below the chip to form an adhesive layer (4); S8, using a precision drilling controller to drill a fluid inlet (5) and a fluid outlet (6) on the substrate (3) on the chip; S9, connecting the lower chip substrate (1) and the upper chip substrate (3) via the adhesive layer (4), and applying pressure to bond the lower chip substrate (1) and the upper chip substrate (3) to obtain a crack chip; S10, installing fluid interfaces (7) at the fluid inlet (5) and the fluid outlet (6) on the surface of the substrate (3) on the chip respectively; S11, injecting deionized water into the crack chip through the fluid inlet (5), and verifying the sealing property of the channel and the fluid flow performance by low pressure; S12. Clean the qualified fracture chip with deionized water and acetone to remove the residual substances in the fracture chip and obtain a real rock fracture microfluidic chip.
4. The method for preparing a transparent calcite-based microfluidic fracture chip according to claim 3, characterized in that: The S1 specifically includes: A thin slice cutting machine is used to cut the selected natural transparent calcite crystal into crystal slices with a size of 2 cm×4 cm and a thickness of 3 mm, and the surface of the crystal slices is polished to obtain a chip lower substrate (1) and a chip upper substrate (3).
5. The method for preparing a transparent calcite-based microfluidic fracture chip according to claim 3, characterized in that: The crack channel (2) in S3 has a length of 3 cm and a depth of 1 mm.
6. The method for preparing a transparent calcite-based microfluidic fracture chip according to claim 3, characterized in that: The S4 specifically includes: The chip lower substrate (1) is immersed in a hydrochloric acid solution, and the acid solution flow is controlled by stirring at 10 rpm / min. The etching time is controlled to be 10 to 15 minutes, until the etching depth and shape reach the expected depth and shape.
7. The method for preparing a microfluidic fracture chip based on transparent calcite according to claim 3, characterized in that: The depth of the fluid inlet (5) and the fluid outlet (6) drilled in S6 is located on the outer wall of the crack channel (2) and does not penetrate the lower substrate (1) of the chip.
8. The method for preparing a transparent calcite-based microfluidic fracture chip according to claim 3, characterized in that: The fluid inlet (5) and fluid outlet (6) drilled in S8 pass through the substrate (3) on the chip.
9. The method for preparing a microfluidic fracture chip based on transparent calcite according to claim 3, characterized in that: The S11 specifically includes: Inject deionized water into the fluid inlet (5) of the crack chip and apply an initial pressure of 0.1 MPa; Closing the fluid outlet (6), maintaining the water pressure in the crack chip stable, recording the initial pressure, and monitoring the pressure decay value in the chip in real time; If the pressure decay value is less than 5% within 30 minutes, and the average pressure decay value is within 5% after the sealing test is repeated 3 times, the crack chip has good sealing performance; The uniformity and speed of the ionized water flow are observed using a fluorescent tracer method. Fluorescent dye is added to deionized water and injected into the fracture channel (2). The flow of the ionized water fluid in the channel is observed using a fluorescent microscope. If the flow trajectory of the fluorescent dye is smooth and uniform without stagnation or backflow, it is determined that the fluidity in the fracture channel (2) meets the requirements.
Citation Information
Patent Citations
Micro-fluidic chip for geological process chemical corrosion study and making method
CN109894170A
Manufacturing method of 3D (three-dimensional) glass plate
CN105152540A
Manufacturing method of real rock specimen having through cracks
CN105606417A
Carbonate reservoir microcosmic model, and preparation method and application thereof
CN112598986A
Method for making internal fracture in natural real rock material and application thereof
CN113933121A